Democratic backsliding as an obstacle in Polish-American cooperation in promoting democracy - Jureńczyk, Łukasz (Polityka i Społeczeństwo, 2022)
The United States has been the main promoter of democratic values in the world for decades. After the Cold War, promoting these values in Central and Eastern Europe, including Poland, was their important strategic goal. Poland, striving for the closest possible relations with the US, joined its efforts to promote democracy in Eastern Europe and other parts of the world. While this had tangible effects in the vicinity of Poland, doing so as part of military missions in Afghanistan and Iraq ended in failure. In recent years, Polish-American cooperation to promote democracy has been limited due to democratic backsliding in Poland. The American authorities have criticized the legal changes in Poland that limit the independence of the judiciary and freedom of the media, as well as other actions that violate the principles of liberal democracy and the rule of law. Criticism has a limited impact on stopping the regression of democracy in Poland. Moreover, with the outbreak of the war in Ukraine, the issue of democratic backsliding has been overshadowed by the military aspects of Polish-American cooperation.